Reconstructing the Minangkabau Customary Prohibition of Intra-Clan Marriage: An Analysis Through Fazlur Rahman’s Double Movement Theory - Syafitri, Anesia; Amri, Ulil; Fithria, Nurul (Al-Mujtahid: Journal of Islamic Family Law, 2025)
This article examines the reconstruction of the Minangkabau customary prohibition of intra-clan marriage (perkawinan sesuku) through Fazlur Rahman’s double movement theory. Historically, the ban served to safeguard the integrity of the matrilineal line, reduce conflict among clans, and preserve social stability within a tightly knit communal order. In contemporary Minangkabau society, however, accelerated migration, urbanization, and higher levels of education have created new marriage patterns and shifted value orientations, so the absolute character of this norm is increasingly questioned, particularly because it lacks explicit textual support in Islamic law. Using qualitative, library-based research, the study first identifies the Qur’anic moral principles governing marriage, kinship limits, and the protection of family honor, then rereads the Minangkabau prohibition as a form of local custom (‘urf) in light of these principles. The analysis shows that the rule can be reformulated from a rigid sacral prohibition into a flexible ethical guideline that still protects lineage (hifz al nasl) and social dignity (hifz al ird), while giving greater recognition to individual rights and contemporary social realities. The article proposes a model of normative reconstruction that places family consultation, genealogical mapping, and communal consensus at the center of decision making, so that the relationship between Islamic law and Minangkabau custom develops toward a more dialogical and context-sensitive harmony.